Aggression and hormones are associated with heterogeneity in parasitism and parasite dynamics in the brown mouse lemur. (October 2017) - Zohdy, Sarah; Bisanzio, Donal; Tecot, Stacey; Wright, Patricia C.; Jernvall, Jukka
Abstract : Animal behaviours, like aggression, can directly affect host health by influencing exposure to parasites. Aggressive individuals may experience an increase in agonistic interactions and contact rates with conspecifics, which might increase their probability of acquiring parasites. However, aggression is not the only factor that shapes parasitism; proximate mechanisms like hormone-modulated immunosuppression can also have broad impacts. Here, we hypothesized that high levels of aggression, cortisol and testosterone would be positively associated with parasitism and that aggressive individuals would play a larger role spreading parasites to conspecifics than would docile individuals. We measured aggression using the level of aggressive response to human handling during capture. Our aim was to examine associations between aggression and hormones (cortisol and testosterone) on variation in endo- and ectoparasitism in a population of wild mouse lemurs ( Microcebus rufus ) over a 3-year period. By tracking the movement of lice (directly transmitted parasites) in the population, we also examined the effect of host aggression on population-wide parasite dynamics. We show that animals with high testosterone and cortisol were more likely to exhibit aggressive behaviours, and cortisol was associated with significantly higher ectoparasite infestations. Aggressive individuals were significantly more infested by lice, and also donated significantly more lice to conspecifics in the population. Taken together, our results offer insight into the individual and population health costs of aggression, and empirical support of a trade-off between aggression and ectoparasitism, which may have driven the evolution of aggression and interactions with conspecifics. Highlights: We examined aggression, hormone levels and parasitism in mouse lemurs. High levels of cortisol and testosterone were associated with aggression. Aggressive lemurs had more lice than docile lemurs. Aggressive lemurs donated more lice to conspecifics. Aggression places mouse lemur health at risk, which may decrease fitness.